High power laser antireflection subwavelength grating on fused silica by colloidal lithography. (25th May 2016) - Ye, Xin; Huang, Jin; Geng, Feng; Liu, Hongjie; Sun, Laixi; Yan, Lianghong; Jiang, Xiaodong; Wu, Weidong; Zheng, Wanguo
Abstract: In this study we report on an efficient and simple method to fabricate an antireflection subwavelength grating on a fused silica substrate using two-step reactive ion etching with monolayer polystyrene colloidal crystals as masks. We show that the period and spacing of the obtained subwavelength grating were determined by the initial diameter of polystyrene microspheres and the oxygen ion etching duration. The height of pillar arrays can be adjusted by tuning the second-step fluorine ion etching duration. These parameters are proved to be useful in tailoring the antireflection properties of subwavelength grating using a finite-difference time-domain (FDTD) method and effective medium theory. The subwavelength grating exhibits excellent antireflection properties. The near-field distribution of the SWG which is directly patterned into the substrate material is performed by a 3D-FDTD method. It is found that the near-field distribution is strongly dependent on the periodicity of surface structure, which has the potential to promote the ability of anti-laser-induced damage. For 10 ns pulse duration and 1064 nm wavelength, we experimentally determined their laser induced damage threshold to 32 J cm −2, which is nearly as high as bulk fused silica with 31.5 J cm −2 .